2016
DOI: 10.1038/srep30068
|View full text |Cite
|
Sign up to set email alerts
|

A fast electrochromic polymer based on TEMPO substituted polytriphenylamine

Abstract: A novel strategy to obtain rapid electrochromic switching response by introducing 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) moiety into polytriphenylamine backbone has been developed. The electrochromic properties of the integrated polymer film are investigated and a possible mechanism is proposed with TEMPO as a counterion-reservoir group to rapidly balance the charges during electrochromic switching, which leads to significantly improved electrochromism performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…However, it is more direct and efficient to clarify the relationship between the ion diffusion process and EC switching time through designing and preparing novel monomer and polymer structures. Zhang et al 14 reported that the introduction of 2,2,6,6tetramethylpiperidine-1-oxyl (TEMPO) moieties at the side chain could significantly improve the switching time of polytriphenylamine derivatives. It was speculated that TEMPO moieties were first oxidized and accumulated doping ions as a counterion reservoir; then, these counterions would transfer to balance the charge of the polymer backbone, resulting in ultrafast color change during oxidization.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is more direct and efficient to clarify the relationship between the ion diffusion process and EC switching time through designing and preparing novel monomer and polymer structures. Zhang et al 14 reported that the introduction of 2,2,6,6tetramethylpiperidine-1-oxyl (TEMPO) moieties at the side chain could significantly improve the switching time of polytriphenylamine derivatives. It was speculated that TEMPO moieties were first oxidized and accumulated doping ions as a counterion reservoir; then, these counterions would transfer to balance the charge of the polymer backbone, resulting in ultrafast color change during oxidization.…”
Section: Introductionmentioning
confidence: 99%
“…Electrochromic (EC) materials have been widely studied and rapidly developed in past decades because of their potential applications in smart windows, autodimming mirrors, adaptive camouflage, and electronic display devices. Among numerous EC materials, organic conjugated polymers with excellent coloration efficiency, high optical contrast, , fast switching time, and color adjustment have attracted a great deal of attention. For EC applications, the polymers are usually prepared as a uniform thin film on an indium tin oxide (ITO) electrode, generally by electropolymerization or spray-/spin-coating methods. A good electroactive site is an essential condition for electrochemical polymerization. , Spray-/spin coating must meet the requirements of complex chemical synthesis, good solubility, and the inability to construct cross-linked polymer structures. , Thus, development of new methods for preparing polymer films for electrochromic applications has been of great significance. , In particular, the development of a simple method to prepare novel conjugated polymer films for electrochromic applications that can be efficiently constructed under mild conditions using readily available precursors is preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Among these reported conjugated polymers, many polymers based on triphenylamine (TPA), which have ultrafast electron‐transfer rate constants and good hole‐transporting abilities, have been studied intensively as electrode materials for organic batteries and SCs . In addition, a large number of TPA‐based polymers exhibit electrochromic behavior during redox processes that have potential applications in ECDs . To improve the charge carrier transport properties and structural stabilities of polymer chains, some thiophene derivatives, such as 2,2′‐bithiophene and 3,4‐ethylenedioxythiophene (EDOT), have been incorporated within the polymer backbone as “bridge” linkages.…”
Section: Introductionmentioning
confidence: 99%